Polarity based characterization of biologically active extracts of Ajuga bracteosa Wall. ex Benth. and RP-HPLC analysis - Syeda Saniya Zahra; Madiha Ahmed; Muhammad Qasim; Bilquees Gul; Muhammad Zia; Bushra Mirza; Ihsan-ul Haq (BMC, 2017)
Abstract Background The concept of botanical therapeutics has revitalized due to wide importance of plant derived pharmaceuticals. Therefore, the ameliorative characteristics of Ajuga bracteosa were studied. Methods Total phenolic content, flavonoid content, antioxidant capacity, reducing power and free-radical scavenging activity were determined colorimetrically. Specific polyphenols were quantified by RP-HPLC analysis. Preliminary cytotoxicity was tested using brine shrimp lethality assay while antiproliferative activity against THP-1 and Hep-G2 cell lines was determined by MTT and SRB protocols respectively. Antileishmanial potential was assessed via MTT colorimetric method. To investigate antidiabetic prospect, α-amylase inhibition assay was adopted whereas disc diffusion method was used to detect likely protein kinase inhibitory, antibacterial and antifungal activities. Results Among fifteen different extracts, maximum total phenolic content (10.75 ± 0.70 μg GAE/mg DW), total reducing power (23.90 ± 0.70 μg AAE/mg DW) and total antioxidant capacity (11.30 ± 0.80 μg AAE/mg DW) were exhibited by methanol extract with superlative percent extract recovery (17.50 ± 0.80% w/w). Chloroform-methanol extract demonstrated maximum flavonoid content (4.10 ± 0.40 μg QE/mg DW) and ethanol extract exhibited greatest radical scavenging activity (IC50 14.40 ± 0.20 μg/ml). RP-HPLC based quantification confirmed polyphenols such as pyrocatechol, gallic acid, resorcinol, catechin, chlorogenic acid, caffeic acid, syringic acid, p-coumaric acid, ferulic acid, vanillic acid, coumarin, sinapinic acid, trans-cinnamic acid, rutin, quercetin and kaempferol. The brine shrimp lethality assay ranked 78.60% extracts as cytotoxic (LC50 ≤ 250 μg/ml) whereas significant THP-1 inhibition was shown by methanol-acetone extract (IC50 4.70 ± 0.43 μg/ml). The antiproliferative activity against Hep-G2 hepatoma cancer cell line was demonstrated by n-hexane, ethylacetate and methanol-distilled water (IC50 8.65-8.95 μg/ml) extracts. Methanol extract displayed prominent protein kinase inhibitory activity (MIC 12.5 μg/disc) while n-hexane extract revealed remarkable antileishmanial activity (IC50 4.69 ± 0.01 μg/ml). The antidiabetic potential was confirmed by n-hexane extract (44.70 ± 0.30% α-amylase inhibition at 200 μg/ml concentration) while a moderate antibacterial and antifungal activities were unveiled. Conclusion The variation in biological spectrum resulted due to use of multiple solvent systems for extraction. We also deduce that the valuable information gathered can be utilized for discovery of anticancer, antileishmanial, antioxidant and antidiabetic bioactive lead candidates.